High-intensity interval training (HIIT) increases insulin-like growth factor-I (IGF-I) in sedentary aging men but not masters' athletes: an observational study. (2nd January 2017) - Herbert, Peter; Hayes, Lawrence D.; Sculthorpe, Nicholas; Grace, Fergal M.
Abstract: Introduction: The aim of this investigation was to examine the impact high-intensity interval training (HIIT) on serum insulin-like growth factor-I (IGF-I) in active compared with sedentary aging men. Methods: 22 lifetime sedentary (SED; 62 ± 2 years) and 17 masters' athletes (LEX; 60 ± 5 years) were recruited to the study. As HIIT requires preconditioning exercise in sedentary cohorts, the study required three assessment phases; enrollment (phase A), following preconditioning exercise (phase B), and post-HIIT (phase C). Serum IGF-I was determined by electrochemiluminescent immunoassay. Results: IGF-I was higher in LEX compared to SED at baseline ( p = 0.007, Cohen's d = 0.91), and phase B ( p = 0.083, Cohen's d = 0.59), with only a small difference at C ( p = 0.291, Cohen's d = 0.35). SED experienced a small increase in IGF-I following preconditioning from 13.1 ± 4.7 to 14.2 ± 6.0 μg·dl −1 ( p = 0.376, Cohen's d = 0.22), followed by a larger increase post-HIIT (16.9 ± 4.4 μg·dl −1 ), which was significantly elevated compared with baseline ( p = 0.002, Cohen's d = 0.85), and post-preconditioning ( p = 0.005, Cohen's d = 0.51). LEX experienced a trivial changes in IGF-I from A to B (18.2 ± 6.4 to 17.2 ± 3.7 μg·dl −1 [ p = 0.538, Cohen's d = 0.19]), and a small change post-HIIT (18.4 ± 4.1 μg·dl −1 [ p = 0.283, Cohen's d = 0.31]). Small increases were observed in fat-free mass in both groups following HIIT ( p < 0.05, Cohen's d = 0.32–0.45). Conclusions: In conclusion, HIIT with preconditioning exercise abrogates the age associated difference in IGF-I between SED and LEX, and induces small improvements in fat-free mass in both SED and LEX.